Theoretical Study on the Composite Floor Made of a Steel Space Frame and Concrete Slab - Najim, Nada Abdulkareem; Saleh, Ihab Sabri; Dakhil, Ammar Jasim (Universitas Muhammadiyah Sidoarjo, 2025)
This study investigates the structural behavior of composite roof systems consisting of a double-layer space frame topped with a concrete slab. The analysis focuses on the influence of joint spacing, connection types (fixed vs. bolted), and the addition of a concrete slab on the overall system performance. Twelve structural models were developed using ETABS (CSI) software, with an equal distribution between slab-incorporated and slab-free configurations. After performing numerical simulations, key parameters, including element cross-sectional areas, vertical deflections, and maximum displacements, were evaluated according to ACI 318 reinforced concrete and AISC steel design standards. The results indicate that incorporating a concrete slab into a space-frame system significantly reduces the maximum vertical deflection and allows for more efficient element sizing, especially in the top chord elements. Furthermore, models with fixed supports demonstrated greater overall stiffness and stability compared to models with pinned connections. The results confirm the critical role of slab integrity and joint stiffness in enhancing structural efficiency, improving material utilization, and ensuring compliance with contemporary design standards.